Transient assembly of precision-tuned platinum-skin intermetallic catalysts for fuel cells - Jia Ding; Tao Zhang; Wanqing Song; Zezhou Li; Xin Wang; Xinyi Yang; Jiahui Feng; Ming Wen; Yanan Chen; Zhong Wu; Jihan Zhou; Bin Liu; et al. (Science, 2026)
Highly efficient catalysts require precisely engineered intricate structures, yet conventional thermodynamically controlled syntheses often involve cumbersome procedures and limited structural precision. We report a nonequilibrium transient assembly strategy for the ultrafast synthesis of intricately structured nanocatalysts, including core-shell platinum (Pt)–skinned intermetallic nanocrystals exemplified by Pt@PtFe-i. By using a periodic thermal-pulse protocol to drive the continuous evolution of high-energy transient PtFe configurations, we achieved the synchronous assembly of a high-order PtFe intermetallic core and an atomic-layer-precise Pt skin. The Pt@PtFe-i catalyst exhibits coordination-dependent compressive strain within the Pt skin, creating a high density of highly active sites for the oxygen reduction reaction. The H 2 -air fuel cell with Pt@PtFe-i delivers a peak power of 1.25 watts per square centimeter at a cathode Pt loading of 0.1 milligrams per square centimeter, with a small peak power loss of 3.2% after 30,000 accelerated durability testing cycles.